Antidiabetic Effect of Ethanol Extract of Keji beling Leaves (Strobhilantes crispa) in Rats Induced by Streptozotocin - Nuraqidah, Nuraqidah; Hasnaeni, Hasnaeni; Mirawati, Mirawati (Hydrogen: Jurnal Kependidikan Kimia, 2024)
Diabetes Mellitus (DM) type 2 is a chronic disease characterized by increased glucose levels in the body due to insulin resistance or inadequate insulin production. This study aims to determine the antidiabetic potential of keji beling ( Strobhilantes crispa) leaf extract. This research is different from other studies which used Alloxan as a diabetes inducer. In this study, Streptozotocin was used as a DM inducer. After treatment, information was obtained that keji beling (S. crispa) extract could reduce blood glucose levels in type 2 DM rats. Experimental research used 30 male Wistar rats divided into six groups consisting of normal group, negative control (HFD and Streptozotocin), positive control (Glibenclamide), dose group I (150 mg/kg BW), dose II (300 mg/ kg BW), and dose III (450 mg/kg BW). Based on the research results, it is known that S.crispa leaf extract can reduce blood glucose levels in mice induced by Streptozotocin and has the potential to act as an antihyperglycemic in type 2 DM.